AJT COGNITIVE TEST: RESPON HARAPAN BARU TERHADAP TES INTELIGENSI ANAK DI INDONESIA - Andi Halima; Eva Meizara Puspita Dewi; Eka Damayanti; Nurfajriyanti Rasyid (Universitas Islam Negeri Alauddin Makassar, 2022)
Problems in the use of psychological tests are often found related to test items that are not culturally sensitive. Language adaptation in psychological tests is not enough to solve these cultural problems. The presence of the AJT Cognitive Test in Indonesia and its use in education is a new hope for the Intelligence test in Indonesia because it is developed according to local culture. Community service activities carried out by APPI Sulawesi in the form of training with the theme